PENGEMBANGAN PSIKOMOTORIK SISWA DALAM PEMBELAJARAN BAHASA ARAB PADA MAHARAH QIRO’AH DI MTs WALISONGO - zainuri, ZAINURI (Lisan An Nathiq : Jurnal Bahasa dan Pendidikan Bahasa Arab, 2023)
Abstract Psychomotor development learning strategies can be the basis of learning methods. psychomotor development which includes skills in the structure of the brain, muscles and nerves as well as the ability to adapt to the environment which makes the speed ratio of the formation of a learning outcome. Reading is the main factor that influences improving the quality of student learning outcomes, so psychomotor development to learn how to read when learning Arabic is also very much needed. And this method is useful in learning Arabic because it can attract students' interest and improve Arabic learning outcomes because learning using this method is not boring. The focus of this research is: (1). How are students' psychomotor development in maharah qiro'ah at MTs Walisongo? (2) What are the student learning outcomes in psychomotor development in Arabic in maharah qiro'ah at MTs Walisongo? This type of research uses qualitative methods. Data collection techniques used were observation, interviews, documentation and tests. With qualitative descriptive analysis techniques and techniques for testing data using triangulation techniques which are reinforced with material taken from references. After going through several stages of the research process, it turned out that the results obtained were quite good. 1. Students become able to read Arabic texts fluently according to the meaning of letters, harakat and Arabic language rules to understand the contents of the text correctly. 2. This learning activity can attract students' interest and enthusiasm when the learning activity takes place. Therefore, this learning method is able to improve student learning outcomes in learning Arabic. Keywords: Psychomotor Development, Arabic Language Learning, Maharah Qiro'ah.